Consul in Japan, 1903-1941 Oswald White's Memoir 'All Ambition Spent'. - Read, Hugo (Renaissance Books, 2017)
A rare account by a foreigner working in Japan in the 20th century; a unique insight into this important period of Japan's history; complements existing material. First a student interpreter, then an assistant in Korea, Vice-Consul in Yokohama and Osaka, Consul in Nagasaki and Dairen, then Consul-General in Seoul, Osaka, Mukden and Tientsin.